The effect of reminiscence therapy on psychological well being of the elderly: A systematic review - Ceacilia Nika Candra Kusuma; Etty Rekawati; Junaiti Sahar; Yossie Susanti Eka Putri (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Aging increases health problems, decreases physical abilities and daily activities that reduce the psychological well-being of the elderly. The aging process is accompanied by psychological problems, such as: increased symptoms of depression, stress, anxiety, and mental well-being problems. Research interventions to improve psychological well-being of elderly have been widely investigated. One of the therapies that has been widely researched and developed is reminiscence therapy, so the research question of the systematic review is how does reminiscence therapy affect psychological well-being of elderly. Purpose: To determine the effect of reminiscence therapy on the psychological well-being of the elderly. Method: A systematic search review of 3 databases: ProQuest, Science Direct, and Wiley Online Library in February 2025 to identify all relevant peer-reviewed journal articles. Based on the search results with the keywords reminiscence therapy and (parents or elderly or elderly) and (psychology of well-being or depression or anxiety or emotional) obtained 63,002. Furthermore, the journal article limiter (scientific journal, the last 5 years 2020-2025, English, nursing psychology journal) obtained 819 articles. Then the screening compiled the title and abstract obtained 23 articles, then the screening by reading the article as a whole obtained 10 articles, after the article criticism/critical assessment was carried out, 8 journals were analyzed in this systematic review. Results: Shows that reminiscence therapy can improve well-being, reduce depression, increase life satisfaction, increase self-esteem, increase meaning in life, increase a sense of cohesion, improve problem-solving skills, reduce anxiety about death, and improve the ability of older adults to adapt to aging.   Conclusion: Reminiscence therapy is effective to improve psychological well-being of the elderly. The application of reminiscence therapy can be carried out in health service practices, both elderly in nursing homes and in the community. Suggestion: It is hoped that a more comprehensive systematic review can be developed by conducting a review of previous literature, searching for articles from various databases, and exploring other sources such as the web and others.